The readability, understandability and actionability of government-provided obstetrics and gynecology patient information sheets - Yvette D. Miller; Olivia Mac; Robert Le Roy; Rachel Thompson (Health Literacy and Communication Open)
Background There are demonstrated deficits in informed consent processes for obstetrics and gynecology procedures. Written patient information can facilitate informed consent. Standardized patient information adjoined to consent forms for a range of obstetrics and gynecology procedures have been developed and made publicly available by the Queensland Government in Australia.Aims We evaluated the readability, understandability and actionability of patient information sheets adjoined to consent forms for obstetrics and gynecology procedures published by the Queensland Government.Methods We analyzed 32 patient information sheets. We assessed readability using the Simple Measure of Gobbledygook (SMOG) index, Flesch Kincaid Grade Level (FKGL) and Flesch Reading Ease (FRE), and understandability and actionability using the Patient Education Materials Assessment Tool (PEMAT). Acceptability thresholds of ≤8 were used for SMOG and FKGL, >60 for FRE and ≥70% for PEMAT.Results Mean SMOG was 13.3 (SD = 0.5; range: 12.3–14.7), FKGL was 10.5 (SD = 0.6; range: 9.1–11.9) and FRE was 46.5 (SD = 2.8; range: 37.7–51.4). No information sheets had acceptable readability. Mean understandability was 61% (SD = 9.3; range: 47–87%) and 3/32 were acceptable. Mean actionability was 55.6% (SD = 13.2; range: 40–80%) and 5/32 were acceptable.Discussion Most Queensland Government obstetrics and gynecology patient information had unacceptable readability, understandability and actionability. Their value for facilitating informed consent may be improved through involving consumers and health literacy experts in their review and development and using established tools to guide design processes.